Simulation and Experimental Study of Waste Cooking Oil to Biodiesel Production and Energy Analysis (Chemical Engineering Research Bulletin, 2023)
Bangladesh heavily relies on imported crude oils for refining. With the fossil fuel crisis, it is vulnerable. Biodiesel from waste cooking oil can be a potential alternative to save foreign currency reserves. This study includes laboratory experiments and process simulation using Aspen HYSYS to produce biodiesel from WCO through transesterification. Biodiesel produced from waste cooking oil (WCO) in the laboratory has similar properties to standard ASTM D6751 and commercial diesel, making it a viable alternative fuel source. The energy analysis showed that WCO-to-biodiesel production is an energy-efficient option for the sustainable management of WCO waste.Chemical Engineering Research Bulletin 23 (2023): 57-62